Ferritin to Erythrocyte Sedimentation Rate Ratio: Simple Measure to Identify Macrophage Activation Syndrome in Systemic Juvenile Idiopathic Arthritis. Issue 6 (13th July 2019) - Eloseily, Esraa M. A.; Minoia, Francesca; Crayne, Courtney B.; Beukelman, Timothy; Ravelli, Angelo; Cron, Randy Q.
Abstract : Objective: Macrophage activation syndrome (MAS) is a life‐threatening complication of systemic juvenile idiopathic arthritis (sJIA). Early diagnosis is critical. Classification criteria for MAS in sJIA perform less well in the setting of cytokine‐directed therapies. The goal herein was to explore a simple ratio of serum ferritin to the erythrocyte sedimentation rate (ESR) for diagnosis of MAS in the setting of sJIA, and to assess ferritin alone as a screening tool for identifying MAS of multiple etiologies. Methods: Data from a large international cohort of sJIA patients with and without MAS, and from hospitalized patients with systemic infection (SI), were assessed for the ferritin:ESR ratio and ferritin alone to identify MAS among sJIA patients. Moreover, data from a smaller cohort of MAS patients associated with multiple etiologies and febrile hospitalized controls were explored. For both cohorts and controls, receiver operating characteristic curves (ROCs) for the ferritin:ESR ratio and ferritin alone were constructed, and areas under the curves (AUCs) were calculated. The Youden index was used to determine the optimal ferritin:ESR ratio and ferritin alone cut points for diagnosis. Results: A ferritin:ESR ratio of 21.5 was 82% sensitive and 78% specific for diagnosing sJIA‐MAS versus active sJIA without MAS. Ferritin alone with a set sensitivity of 95% (screening tool) had an 89.3% specificity of identifying all‐cause MAS versus febrile hospitalized children. Conclusion: The ferritin:ESR ratio is a practical tool for diagnosing MAS among sJIA patients, and serum ferritin alone is a remarkable screening tool for identifying MAS among febrile hospitalized children.